2007
DOI: 10.1097/mbp.0b013e32809efa02
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular (LV) geometry and dipping state are determinants of LV mass reduction with angiotensin-converting enzyme inhibitor antihypertensive treatment

Abstract: In essential hypertension, left ventricular geometry and dipping state are independent determinants of left ventricular mass reduction with angiotensin-converting enzyme inhibitor treatment. All angiotensin-converting enzyme inhibitors are efficient in decreasing left ventricular mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…8,9,[11][12][13][14]39 Recent data support that quinapril and captopril are equally efficient in modifying important surrogate end points with prognostic significance, such as left ventricular mass. 11 On the other hand, some studies have underscored that an improvement of arterial function in hypertensives may benefit prognosis, 5,7 but there are no trials to directly compare different ACEIs with regard to outcomes. Our findings cannot guide chronic antihypertensive treatment, and they do not suggest, by any means, that quinapril is a better antihypertensive drug.…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,[11][12][13][14]39 Recent data support that quinapril and captopril are equally efficient in modifying important surrogate end points with prognostic significance, such as left ventricular mass. 11 On the other hand, some studies have underscored that an improvement of arterial function in hypertensives may benefit prognosis, 5,7 but there are no trials to directly compare different ACEIs with regard to outcomes. Our findings cannot guide chronic antihypertensive treatment, and they do not suggest, by any means, that quinapril is a better antihypertensive drug.…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%
“…5 Likewise, there are data showing that the reversal of endothelial dysfunction, that is present in hypertensive patients, 6 may benefit prognosis. 7 Drugs that block the renin-angiotensin system (RAS), such as angiotensin converting enzyme (ACE) inhibitors (ACEIs), may improve cardiovascular structure and function, [8][9][10][11][12][13] and this effect is not fully explained by the respective BP change. [8][9][10]12,14 However, different ACEIs may not confer a same degree of organoprotection, and this is perhaps due to dissimilarities in their propensity to penetrate vascular tissue and inhibit the tissue ACE.…”
Section: Introductionmentioning
confidence: 99%
“…One alternative is to use short fixed clock-time intervals, which eliminate the transition periods in the morning and evening during which the blood pressure rapidly changes in most subjects. 59 The daytime and nighttime blood pressures defined in this way approximate within 1 to 2 mm Hg to the awake and asleep blood pressures. 59 In defining the clock-time intervals, one should account for differences in lifestyle across different cultures.…”
Section: How To Measure Daytime and Nighttime Blood Pressure?mentioning
confidence: 99%
“…59 The daytime and nighttime blood pressures defined in this way approximate within 1 to 2 mm Hg to the awake and asleep blood pressures. 59 In defining the clock-time intervals, one should account for differences in lifestyle across different cultures. 29 Although the last European guideline recommends that proportionally to the duration of daytime and nighttime the number of valid blood pressure readings should be similar, 58 it is common practice to space the readings at a greater interval during the night in order not to impair sleep quality.…”
Section: How To Measure Daytime and Nighttime Blood Pressure?mentioning
confidence: 99%
“…In addition, the study reported “impaired left ventricular geometry and blunted nocturnal blood pressure fall before treatment” as significant predictors of LVH regression. The researchers did not find any correlation with diabetes 12 . However, it is known that hypertensives with diabetes have greater LV mass 13-15 .…”
Section: Discussionmentioning
confidence: 84%